Characterization of a promoter and a transcription terminator of Spiroplasma melliferum virus SpV4. - Stamburski, C (1990)
Spiroplasma virus 4 (SpV4) is an isometric virus with single-stranded, circular DNA infecting the helical mollicute Spiroplasma melliferum, a honeybee pathogen. Previous studies in our laboratory led to the determination of the base sequence of the SpV4 DNA. Nine open reading frames and three promoterlike sequences (P1, P2, and P3) were identified. An inverted repeat leading to the formation of a hairpin structure on the transcription product was also found and predicted to be a transcription terminator (T). We have now studied the in vivo transcription of the SpV4 genome by Northern (RNA) blot analysis of the total RNAs extracted from SpV4-infected spiroplasma cells. Transcripts of 7.8, 4.4, 3.4, and 2.7 kilobases (kb) were detected. The 3.4-kb RNA was the major transcript. The 5' and 3' ends of this transcript were determined by S1 mapping and primer extension. Characterization of the 3' end by S1 mapping showed that the 3.4-kb transcript terminates within the stretch of uridine residues following the hairpin structure of terminator T. Characterization of the 5' end by S1 mapping indicated that transcription proceeds from a newly recognized promoter, P0, located 36 nucleotides upstream of P1. Primer extension resulted in two cDNA signals. The short cDNA was probably a primer extension artifact due to the presence of a hairpin structure on the transcript. When reverse transcriptase stopped at this hairpin or read through, the short or the long cDNA, respectively, was obtained. The size of the long cDNA identified P0 as the transcription promoter. Promoter P0 was also shown to be functional in Escherichia coli. Indeed, when inserted upstream of the chloramphenicol acetyltransferase gene of a promoter selection vector, it promoted transcription of this gene. As in the case of S. melliferum, two cDNAs were obtained by primer extension, the longer cDNA identifying P0 as the promoter.